Prediktor Kegagalan Intervensi Koroner Perkutan pada Oklusi Total Koroner Kronik di Pusat Jantung Nasional, Indonesia - I Gumiwang; Muhammad Munawar; RWM Kaligis (The Indonesian Heart Association, 2007)
Background. Percutaneous Coronary Intervention (PCI) in patients with Chronic Total Coronary Occlusion (CTO) is associated with higher rate of failure and higher rate of complication compared to non-CTO angioplasty. Improvement in technique, logistic and patient’s selection method lead to a better success rate. Identification of predictor of failure could be an important step in patient selection. The aim of the study is to know the predictors of failure of PCI in patients with CTO.Methods and results. A retrospective analysis of clinical and angiographic data of 78 consecutive eligible CTO patients who underwent PCI selected in series of 1205 total occluded vessel of 3654 angiographic patients in the year of 2005 in our catheterization laboratory. We analysed 25 variables, 12 clinical variables (age, sex, family history, smoking, diabetes mellitus, hypertension, history of myiocardial infarction, history of coronary bypass operation, age of occlusion >1 year, severe angina and poor left ventricle systolic dysfunction)and 13 angiographic variables (true CTO, CTO location, ostial lesion, calcification, tortousity, non-tapered type, side branch type, bridging collateral, diffuse disease, vessel diameter < 3mm, CTO length > 15mm, multi-lesion and multi vessel disease)by univariate and multivariate analysis (logistic regression) in association between 21 cases of procedural failure group and 57 cases of procedural success group. Procedural success was achieved in 57 patients (73%) and complication occured in one patient (1%). Majority of patients are male with mean age 55 year. Presence of calcification is the only predictor identified by univariate analysis (OR 3,28. p 0,04. 95%CI 1.05-10,18). Multivariate analysis identified multivessel disease (OR 7,1. p 0,07 .95%CI 0,85-59,21) and diffuse disease (OR 2,7. p 0,06 .95%CI 0,93-8,08) as predictors of procedural failure.Conclusions. We identified multivessel disease and diffuse disease as two predictors of procedural failure of PCI in our series of CTO patients with 73% success rate and 1% complication rate in the year of 2005.